Fruit quality and yield of ‘Imperial Gala’ apple trees protected by anti-hail nets of different colorations in southern Brazil - Do Amarante C.V.T.* (2018)
Covering apple orchards with nets to protect from hailstorms changes the amount and quality of the light supplied to the trees. This study was carried out to assess the effects of shading provided by protection nets with different colorations on fruit quality and yield of apple trees in southern Brazil, along four growing seasons. ‘Imperial Gala’ apple trees (on M7 rootstock, raised as slender spindles, with a spacing of 5×2 m) were left uncovered (control) or covered with crystal (transparent), white, red, blue or black nets (all nets with mesh size of 4.0×7.0 mm). The black net caused the more substantial reduction of photosynthetically active radiation (PAR; λ=400-700 nm) accumulated over the trees’ canopy along the day (21.0%) in comparison to the uncovered area, followed by blue (18.9%), white (18.4%), red (14.8%) and crystal (14.4%) nets. The black net reduced skin red color, soluble solids content and weight of the fruit at harvest in comparison to uncovered trees. Flesh firmness, severity of russet, density and number of seeds/fruit were not affected by covering the orchards with different nets. Crystal net increased fruit weight and red net increased the number of fruit on the tree in comparison to the control (uncovered trees). The results show that covering the orchard with crystal and red nets increases fruit yield without detrimental effects on fruit quality attributes (color and maturity) at harvest of ‘Imperial Gala’ apple trees cultivated in southern Brazil.